2019
DOI: 10.1111/are.13938
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lactobacillus acidophilus supplementation on growth performances, digestive enzyme activities and gut histomorphology of striped catfish (Pangasianodon hypophthalmus Sauvage, 1878) juveniles

Abstract: The influence of dietary supplementation of Lactobacillus acidophilus, on growth performance, digestive enzyme activities, gut histomorphology and gut microflora were evaluated in juveniles striped catfish (Pangasianodon hypophthalmus). Five experimental diets were formulated by supplementing 0, 10 3 , 10 5 , 10 7 and 10 9 CFU/g L. acidophilus in fishmeal and casein-based semi-purified diet. Triplicate groups of striped catfish (21.69 ± 0.18 g) were stocked in 15 fiberglass tanks with stocking density of 25 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 52 publications
(65 reference statements)
2
11
1
1
Order By: Relevance
“…In this study, the viability of LAB coated feed upon storage was investigated. The results were in accordance with two studies where there was no major decrease in viability of probiotics fortified feed although with a decreasing trend in viability over storage time was obtained (Wanka et al, 2018;Akter et al, 2019). To improve viability, adjustment on the product properties can be made.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the viability of LAB coated feed upon storage was investigated. The results were in accordance with two studies where there was no major decrease in viability of probiotics fortified feed although with a decreasing trend in viability over storage time was obtained (Wanka et al, 2018;Akter et al, 2019). To improve viability, adjustment on the product properties can be made.…”
Section: Discussionsupporting
confidence: 90%
“…Thus results of these studies are in agreement with trends observed in the present study. In Pangasianodon hypophthalmus when fed with L. acidophilus for a period of 12 weeks the total bacterial count in intestine were statistically similar in all the probiotic fed groups and control group (Akter et al 2019). This is in contrast to results of present study.…”
Section: Microbial Analysiscontrasting
confidence: 99%
“…Lactobacillus sp. is gram positive bacteria that able to secrete a wide variety of exogenous enzyme that improve digestion process by increasing intestine enzymatic activity (Akter et al 2019). They observed intake of L. acidophilus linked to increasing lactic acid bacteria resulting changes the amylase and lipase activity.…”
Section: Discussionmentioning
confidence: 99%